Development of a bent Laue beam‐expanding double‐crystal monochromator for biomedical X‐ray imaging. (12th March 2014) - Martinson, Mercedes; Samadi, Nazanin; Belev, George; Bassey, Bassey; Lewis, Rob; Aulakh, Gurpreet; Chapman, Dean
<x xml:space="preserve">Abstract</x> The Biomedical Imaging and Therapy (BMIT) beamline at the Canadian Light Source has produced some excellent biological imaging data. However, the disadvantage of a small vertical beam limits its usability in some applications. Micro‐computed tomography (micro‐CT) imaging requires multiple scans to produce a full projection, and certain dynamic imaging experiments are not possible. A larger vertical beam is desirable. It was cost‐prohibitive to build a longer beamline that would have produced a large vertical beam. Instead, it was proposed to develop a beam expander that would create a beam appearing to originate at a source much farther away. This was accomplished using a bent Laue double‐crystal monochromator in a non‐dispersive divergent geometry. The design and implementation of this beam expander is presented along with results from the micro‐CT and dynamic imaging tests conducted with this beam. Flux (photons per unit area per unit time) has been measured and found to be comparable with the existing flat Bragg double‐crystal monochromator in use at BMIT. This increase in overall photon count is due to the enhanced bandwidth of the bent Laue configuration. Whilst the expanded beam quality is suitable for dynamic imaging and micro‐CT, further work is required to improve its phase and coherence properties.